Biobased acrylic pressure-sensitive adhesives. (June 2021) - Droesbeke, Martijn A.; Aksakal, Resat; Simula, Alexandre; Asua, José M.; Du Prez, Filip E.
Abstract: The ever-increasing regulations within the adhesives industry and the continuous demand for more sustainability, have led to the development of environmentally more suitable alternatives to petroleum-based pressure-sensitive adhesives (PSAs). This review provides an overview of the current strategies and methods to develop sustainable, acrylic PSAs derived from renewable resources, such as vegetable oil, lignin, carbohydrates and terpenes. Herein, we emphasize some of the key concepts in the literature within the past decades, which paved the way to the current focus of improving the adhesive properties by employing the full array of natural building blocks. In this context, some recent strategies that give tailor-made adhesive properties to PSAs are also discussed, in view of the desired application. With this critical insight on the large set of research efforts in the context of biosourced acrylic PSAs, we aim to provide a guide for new researchers in this highly emerging field. Graphical abstract: Image, graphical abstract